Mapping the force field of a hydrogen-bonded assembly - Sweetman, Adam; Jarvis, Samuel Paul; Sang, Hongqian; Lekkas, Ioannis; Rahe, Philipp; Wang, Yu; Wang, Jianbo; Champness, Neil R.; Kantorovich, Lev; Moriarty, Philip (Nature Publishing Group, 2014)
Hydrogen bonding underpins the properties of a vast array of systems spanning a wide variety of scientific fields. From the elegance of base pair interactions in DNA to the symmetry of extended supramolecular assemblies, hydrogen bonds play an essential role in directing intermolecular forces. Yet fundamental aspects of the hydrogen bond continue to be vigorously debated. Here we use dynamic force microscopy (DFM) to quantitatively map the tip-sample force field for naphthalene tetracarboxylic diimide molecules hydrogen-bonded in two-dimensional assemblies. A comparison of experimental images and force spectra with their simulated counterparts shows that intermolecular contrast arises from repulsive tip-sample interactions whose interpretation can be aided via an examination of charge density depletion across the molecular system. Interpreting DFM images of hydrogen-bonded systems therefore necessitates detailed consideration of the coupled tip-molecule system: analyses based on intermolecular charge density in the absence of the tip fail to capture the essential physical chemistry underpinning the imaging mechanism.